Student spin-off intentions in malaysian higher educational institutions: Founders characteristics and university roles - Zahari A.R.; Tamyez P.F.M.; Azizan N.A.; Hashim F. (Allied Business Academies, 2023)
This study aims to examine the effects of founders characteristics and university roles on student spin-off intentions in Malaysian higher educational institutions. The study of student spin-offs has captured the attention of policymakers, educators and researchers because of its contribution to achieving a universitys vision and mission, regional economic growth, knowledge commercialization and employment generation. This study involved online survey research designed and informed by two research questions. A stratified sampling technique was applied and was able to obtain 369 samples from the founders of student spin-offs from eleven public universities in Malaysia. The data was analysed using partial least squares-structural equation modelling (PLS-SEM). The results indicate that four of the six paths in the conceptual model were significant and affirmed the direction proposed by this study. The need for achievement, innovativeness, a propensity for risk taking and self-efficacy were seen to be positively related to student spin-off intentions. However, two constructs, namely locus of control and university roles were not significant in relation to student spin-off intentions. This study will provide valuable insights for policymakers and universities enable them to reduce the number of unemployed graduates and create a viable entrepreneurial ecosystem within the universities. The majority of student spin-off studies have been conducted in developed countries so this study could offer different insights from previous studies because the setting is a developing country. 2018, Allied Business Academies. All rights reserved.